2021
DOI: 10.3389/fpsyt.2021.789554
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Traumatic Distress and Its Relationship to Resilience and Coping Among Medical Students in Malaysia During COVID-19 Lockdown

Abstract: Background: Medical students are not spared from the challenges related to the Covid-19 lockdown. The fear and uncertainties may lead to traumatic symptoms and test their resilience and sense of coping. Thus, this study aims to determine the prevalence of peri-traumatic distress symptoms and its association with the level of resilience and the coping strategies used during the lockdown among medical students.Materials and Methods: This was a cross-sectional online questionnaire survey involving medical student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…The recent literature that has been interested in investigating the impact of the COVID-19 pandemic on young adult university students’ psychological well-being has reported a worrying increase in psychopathological symptoms [ 20 , 21 ] and IA [ 17 , 18 ]. Consequently, this study aimed to further increase the knowledge on the possible relevant risk and/or protective factors that may exacerbate or mitigate the effect of the pandemic on the psychopathological risk and the IA risk among young adult university students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent literature that has been interested in investigating the impact of the COVID-19 pandemic on young adult university students’ psychological well-being has reported a worrying increase in psychopathological symptoms [ 20 , 21 ] and IA [ 17 , 18 ]. Consequently, this study aimed to further increase the knowledge on the possible relevant risk and/or protective factors that may exacerbate or mitigate the effect of the pandemic on the psychopathological risk and the IA risk among young adult university students.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the government of Italy and most states around the world recommended the remote switching of academic activities, including distance-learning classes, access to online books, the shift to online assessments, and the cancellation of in-person graduation ceremonies. Many students have shown difficulties in adapting functionally to these challenges, manifesting more concerns about their academic performances [ 19 ] and an increase in post-traumatic stress disorder-like symptoms, defined in terms of peritraumatic distress symptoms (e.g., anxiety and depressive symptoms, specific phobia, avoidance behaviors, and compulsive behaviors) [ 20 , 21 ]. Notably, the pre-pandemic studies widely showed the comorbidity between IA and other psychological problems, especially depression and anxiety symptoms [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…large-scale return to work, economic recovery, increases in workloads), while the pandemic control situation was still unstable with emergence of sporadic cases and local resurgences (Shi et al ., 2021 a ). The instability might arouse senses of uncertainty and insecurity, which in turn enhanced psychological vulnerability (Mohamed et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that in the aftermath of initial peak, general population not only showed greater psychological vulnerability, but also had special psychopathological structures warranting different intervention strategies. The greater centrality of anxiety and somatic symptoms during this phase might be attributable to senses of uncertainty caused by social instability (Mohamed et al ., 2021 ). Our findings indicate that special attention should be paid to this specific period.…”
Section: Discussionmentioning
confidence: 99%